Dental implants in large animal models with experimental systemic diseases: A systematic review - Matos, Flávia Gomes; Stremel, Anna Clara Abreu; Lipinski, Leandro Cavalcante; Cirelli, Joni Augusto [UNESP]; dos Santos, Fábio André (SAGE Publications, 2023)
This systematic review aims to identify and discuss the most used methodologies in pre-clinical studies for the evaluation of the implementation of dental implants in systemically compromised pigs and sheep. This study provides support and guidance for future research, as well as for the prevention of unnecessary animal wastage and sacrifice. Preferred Reporting for Systematic Reviews and Meta-Analyses (PRISMA) was used as a guideline; electronic searches were performed in PubMed, Scopus, Scielo, Web of Science, Embase, Science Direct, Brazilian Bibliography of Dentistry, Latin American and Caribbean Literature in Health Sciences, Directory of Open Access Journals, Database of Abstracts of Reviews of Effects, and gray literature until January 2022 (PROSPERO/CRD42021270119). Sixty-eight articles were chosen from the 2439 results. Most studies were conducted in pigs, mainly the Göttinger and Domesticus breeds. Healthy animals with implants installed in the jaws were predominant among the pig studies. Of the studies evaluating the effect of systemic diseases on osseointegration, 42% were performed in osteoporotic sheep, 32% in diabetic sheep, and 26% in diabetic pigs. Osteoporosis was primarily induced by bilateral ovariectomy and mainly assessed by X-ray densitometry. Diabetes was induced predominantly by intravenous streptozotocin and was confirmed by blood glucose analysis. Histological and histomorphometric analyses were the most frequently employed in the evaluation of osseointegration. The animal models presented unique methodologies for each species in the studies that evaluated dental implants in the context of systemic diseases. Understanding the most commonly used techniques will help methodological choices and the performance of future studies in implantology.
Keywords: animal models; diabetes mellitus; Osseointegration; osteoporosis